Anxiolytic-Like Effects of Extremely Low Frequency Electric Field in Stressed Rats: Involvement of 5-HT2C Receptors - Kantar, Deniz; Acun, Alev Duygu; AFŞAR, EBRU; Yargıçoğlu, Piraye (Taylor & Francis Ltd., 2022)
Background Possible modulatory effects of noninvasive brain stimulation have gained interest recently. In our study, the effect of low frequency electric fields (LF-EF) on stress-induced electrophysiological, behavioral changes and the possible involvement of serotonergic 5-HT2C receptors were investigated. Materials and methods A total of eight groups including the control groups were formed by applying LF-EF with or without a 5-HT2C receptor agonist to naive or acute stress exposed rats to demonstrate the effects of LF-EF. LF-EF administration at 10 kV/m was started 30 min before acute stress application and lasted for 1 h in total. Anxiety levels and social interaction were evaluated using the elevated plus maze test and social interaction test, respectively. Auditory evoked potentials (AEP) were recorded by using ascending loudness paradigms. Loudness dependence AEP (LDAEP) was calculated by using amplitude values to analyze serotonergic transmission. Serotonin and glucocorticoid levels were measured in the frontal cortex and hippocampus. Results It was observed that the applied LF-EF reduced the anxiety behavior, and attenuated the LDAEP responses in stress and/or 5-HT2C receptor agonist applied groups. In parallel, an increase in serotonin levels and a decrease in glucocorticoid levels were observed. However, LF-EF exposure was ineffective in impaired social interaction. Conclusions Our findings show that 10 kV/m LF-EF administration may modulate the neural network and physiological responses associated with mild acute stress. 5-HT2C receptor dependent functions are thought to play a role in the anxiolytic effect of LF-EF.
Keywords: Stress; Low Frequencyelectric Field; Serotonin; Auditory Evoked Potentials; Anxiety; Social Interaction